Son - Lowry, Lois.; Lowry, Lois.; Lowry, Lois.; Lowry, Lois. (Boston : Houghton Mifflin Harcourt, 2014)
Unlike the other Birthmothers in her utopian community, teenaged Claire forms an attachment to her baby, feeling a great loss when he is taken to the Nurturing Center to be adopted by a family unit.
Companion book to: The Giver, Gathering blue, and Messenger.
Young Adult
Keywords: Mother and child -- Juvenile fiction; Separation (Psychology) -- Juvenile fiction; Mother and child -- Fiction; Separation (Psychology) -- Fiction; Science fiction; Mother-child relationship -- Fiction; Science fiction; Science fiction